Medical personnel versus the others: comparative assessment for adverse effects of facemasks use during covid-19 in Turkey - TURHAN, GÜLDEN; ÖZBEK, AHMET (My University, 2022)
The study is focusing on the judgements regarding the adverse effects of facemask use during the COVID-19 outbreak. Not only medical personnel but also the general public are bound to wear masks protecting them from highly transmissible diseases. The question to look for the answer is how medical personnel\"s complaints related to these facemasks differ compared to others. The online survey was applied to 675 respondents residing in Istanbul, Turkey. The complaints experienced in 377 medical personnel were inability to wash the face comfortably, headache, difficulty breathing, sweating, excessive hot flashes, not being recognized by the surrounding people, and to damage the face. The complaints reported by 298 general public were difficulty breathing, sweating, excessive hot flashes, and to damage the face. The side effects such as allergic effects, difficulty to wear on and take off the mask, feeling ugly when the mask is on the face, and perceiving high-priced were not felt much by the whole participants in the survey. They all were ambivalent on some effects that were thirsty feeling, the feeling of repression associated with the forced wearing of the mask and inability to see one\"s around on the road easily. Complaints differing significantly in the general public and medical staff include the inability to wash face comfortably, headache, thirsty feeling, allergic effect, high priced perception, damaging face, and inability to see one\"s around easily when one was on the road. For all negative effects caused by mask use, medical personnel had more strongly complaints in comparison with the others.
Keywords: Tekstil Mühendisliği ve Teknolojisi; Tekstil Malzemeleri; Mühendislik ve Teknoloji; Textile Engineering and Technology; Textile Materials; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Malzeme Bilimi; MALZEME BİLİMİ, TEKSTİL; Engineering, Computing & Technology (ENG); MATERIALS SCIENCE; MATERIALS SCIENCE, TEXTILES